Foreign fund flows and equity prices during the Covid-19 pandemic: Evidence from India - Viral V. Acharya; V. Ravi Anshuman; K. Kiran Kumar (Asian Development Bank Institute (ADBI), 2022)
We study the period of the COVID-19 pandemic to assess the impact of foreign institutional investor (FII) flows on asset prices in an emerging market. Using a dataset of stock-level foreign fund flows of Indian equities, we show that stocks experiencing abnormally high innovations in foreign fund flows face a permanent price increase (an "information" effect), whereas stocks experiencing abnormally low (negative) innovations in foreign fund flows suffer a partly transient price decline. During the COVID-19 pandemic, immediate price effects were exaggerated and followed by higher transient volatility. Our methodology shows the efficacy of stabilization policies, initiated notably by the Federal Reserve, in dampening this relationship of foreign fund flows and equity prices in the immediate aftermath of the COVID-19 pandemic. We find the price effects of the FII flows in the pre-stabilization phase to be similar to those during the earlier crisis periods of the taper tantrum and the global financial crisis.
Keywords: F21; G11; G14; G15; 330; foreign institutional investors (FIIs); foreign ownership; portfolio flows; price impact; taper tantrum; VIX; volatility